PENERAPAN PEMBELAJARAN KOOPERATIF MODEL EXAMPLES NON EXAMPLES DAN STAD PADA MATA KULIAH STRUKTUR HEWAN PROGRAM STUDI PENDIDIKAN BIOLOGI - Widowati, Hening (Bioedukasi Jurnal Pendidikan Biologi, 2011)
The research aims to overcome learning difficulties by implementing cooperative learning model âExamples and Non Examples STADâ through activity Lesson Study in Animal Structure college activities. Preliminary research by studying the documentation, observation, and limited interviewsÂ  to faculty and students about the usual lectures in Biology Education courses. Retrieval of data using the method of documentation, observation, tests, and interviews. Data were analyzed descriptive qualitatively. Preliminary research findings indicate that the material is abstract and the Basic Tissues are not related to daily life so it needs to concretisation process ; classes force lecturers held a Biology major classical learning, making it more difficult for understanding because students tend to be a listener only and not make the learning process. To overcome the disadvantages of learning in the college made the development of media in the form of a slides lecture that was presented on the LCD, especially for concreting material, students completed worksheets to conduct discussions and small group work activities, sheet test to determine student understanding, and cooperative learning model performed Examples of Non Examples and STAD through Lesson Study activities at the college activities by empowering collaborative work in small groups. Use of the method in this lecture can improve learning activities that were previously only 38.916% to about 73.930 to 77.833%, and all indicators of learning activities can be achieved. The results of the previous lecture that the average score of only 57.759 to 77.155 on Lesson Study2, so the increased is 33.581%. Based on the data obtained can be concluded implementation of cooperative learning model Examples and Non Examples STAD through Lesson Study in Animal Structure college activities can be a solution to overcome the difficulties learning materials Basic Tissues, which demonstrated the increased activity and student learning outcomes.Kata kunci: examples non examples, STAD, struktur hewan, lesson study